Supplementation of Protein at Breakfast Rather Than at Dinner and Lunch Is Effective on Skeletal Muscle Mass in Older Adults - Kim, Hyeon-Ki; Chijiki, Hanako; Fukazawa, Mayuko; Okubo, Jin; Ozaki, Mamiho; Nanba, Takuya; Higashi, Seiichirou; Shioyama, Miho; Takahashi, Masaki; Nakaoka, Takashi; Shibata, Shigenobu (Frontiers in Nutrition, 2021)
Background: The effects of different intake patterns of meal protein on muscle mass have not been clarified. We cross-sectionally and longitudinally examined the effect of different timing of protein intake on sarcopenia-related factors in older adults. Methods: This cross-sectional study 1 included 219 (male, n = 69, female, n = 150) elderly subjects aged ≥ 65 years. Subjects who consumed more protein at breakfast than at dinner were grouped into the morning group (MG, n = 76; male, n = 26; female, n = 50), and those who consumed more protein at dinner than at breakfast were grouped into the evening group (EG, n = 143; male, n = 43; female, n = 100). In cross-sectional study 2-1 (female, n = 125), the subjects were classified into four groups according to the number of meals with sufficient protein intake. In cross-sectional studies 2-2 (female, n = 125) and 2-3 (female, n = 27), the subjects were classified into eight groups and three groups according to whether they had consumed sufficient protein at three meals; sarcopenia-related factors were compared. The intervention study was a placebo-controlled, double-blind, randomized controlled trial that included 40 elderly women with low daily breakfast protein intake. The subjects were divided into four groups: morning protein and placebo intake groups and evening protein and placebo intake groups. Each group consumed the test food (containing 10 g milk protein) or placebo in the morning or evening for 12 weeks. Blood indices and physical function were assessed before and after the intervention. Results: Comparing all subjects, MG showed significantly higher handgrip strength than did EG (P < 0.05). The higher ratio of morning protein intake relative to the total protein intake, the better the muscle mass (r = 0.452, P < 0.05) and handgrip strength (r = 0.383, P < 0.05). The intervention study showed an increase in muscle mass with the intake of milk protein in the morning rather than in the evening (P < 0.05). Conclusions: Protein intake at breakfast might have relatively stronger effects on skeletal muscle mass than at lunch and dinner. full details.